Karakteristik Fisikokimia, Organoleptik, dan Kandungan Gizi Mayones Minyak Ikan Lemuru (Sardinella sp.) - Arifah, Nazhry Zahra; Alamsjah, Mochammad Amin; Sulmartiwi, Laksmi (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Mayonnaise is a semi-solid emulsion processed product that has a very high fat content because the basic ingredients consist of vegetable oil (70-80%) and egg yolk (15-20%). Generally, mayonnaise has a high fat and calorie content. High fat content if consumed excessively will cause various diseases such as cholesterol, coronary heart disease and the risk of obesity. The use of lemuru fish oil as a substitute for mayonnaise is still rarely done. The protein content in lemuru fish is high enough that can be used as a source of protein. In addition to protein, lemuru fish oil is also enriched by the PUFA content of DHA of 30.10%. The aim of this research was to determine the quality of mayonnaise based on the organoleptic value and stability of the lemuru fish oil mayonnaise emulsion after a shelf life test. Proximate fat analysis using the Soxhlet method, protein analysis using the Kjeldahl method, ash analysis using a furnace, crude fiber analysis using the gravimetric method, water content analysis by evaporating the water in the material using an oven, carbohydrate analysis using the differential method. Shelf life test using the Accelerated Shelf Life Test method. Organoleptic testing uses a hedonic scale (1-5), with a total of 30 panelists. Emulsion stability test using a centrifuge by calculating the volume of oil separated. This study used a factorial randomized block design with two factors, namely temperature (5, 25, 35Â°C) and time (7, 14, 21 days). Mayonnaise proximate results from all parameters have met SNI except for fat and calorie parameters which tend to be lower than SNI standards. The ANOVA test results showed significant differences in organoleptic color and aroma, but it did not show significant differences in organoleptic texture and mold. The best organoleptic results at one-week storage. The emulsion stability results showed significant differences due to temperature and storage time factors.The best emulsion stability results at one week storage at 5, 25 and 35Â°C with a value of 100%.